Proposals for the development of the system of taxation of transport tax (passenger car transport) - A. M. Terekhov (Статистика и экономика, 2019)
The purpose of the study is to analyze the current system of transport taxation and develop proposals for its improvement. The article is devoted to the identification of ways to improve the system of taxation of transport tax on road transport in the Russian Federation, including the optimization of the current method of calculating the tax.Materials and methods. The article analyzes the literary sources of normative, reference and scientific literature on the organization of transport taxation. Based on the analysis of normative legal documentation the method of calculation of the transport tax on the automobile transport oper-ating in the Russian Federation is opened, shortcomings are revealed and the directions of its im-provement are designated. The statistical analysis of indicators of the taxation by the transport tax in the Russian Federation and Nizhny Novgorod Region is carried out. The authors also present statis-tical data on fuel prices in dynamics for three years, interrelation between the increase in the cost of fuel and the increase in fuel excises has been found. A generalization of the accumulated experience in the field of transport tax taxation in Russia and in foreign countries is given. The source data for this research were the materials of the report in the forms: 5-TN (2014-2017), NOM-1 (2014-2018), Internet information resources – бензин.рф and www.gks.ru.Results. This article highlights the features of the current system of taxation of transport tax, the importance of transport taxation for the formation of regional budgets. The inexpediency of replacing the transport tax with fuel excise is justified. The modified method of calculation of the transport tax on automobile transport, including for hybrid cars is developed. The values of the coefficients of environmental friendliness, market value, weight are proposed. In the process of analysis of statistical indicators of taxation the general trend of growth of tax revenues from individuals, reducing revenues from organizations was revealed. The tendency of fuel cost and fuel excise rates increase is established. The percentage ratio of the formation of the tax base for transport tax between taxpayers – legal entities and individuals is established. Conclusion. The use of the proposed methodology in practice will contribute to the implementation of the following regulatory principles of taxation: fairness, economic feasibility; as well as create the prerequisites for improving the environmental situation in the country by redirect-ing part of the funds from taxation to environmental funds. In this aspect, it is assumed that in view of the application of environmental coefficients, taxpayers will seek to upgrade their vehicles with more environmentally friendly, technical re-equipment of vehicles with modern and high environ-mental standards units. If the purpose of transport taxation is given, part of the collected funds can be directed to the development of transport infrastructure. The development of the tax system is an important area of the tax policy of the Russian Federation, as the optimization of the tax burden will contribute to the development of business, which will certainly have a positive impact on the financial and economic performance of enterprises in all spheres of activity.